New additions to the hydroids (Cnidaria: Hydrozoa) from the fjords region of southern Chile - Galea, Horia R.; Häussermann, Verena; Försterra, Günter (Zootaxa, 2009)
We report upon eleven species of thecate hydroids collected during a recent scientific expedition to the North Patagonian Zone between southern Chiloé and Puyuguapi fjord/ Magdalena Island. One species belongs to the family Haleciidae Hincks, 1868, four to the family Sertulariidae Lamouroux, 1812, and six to the family Campanulariidae Hincks, 1868. Of them, Halecium cymiforme Allman, 1888 and Symplectoscyphus leloupi El Beshbeeshy, 1991 are redescribed based on new, fertile material. Sertularella allmani Hartlaub, 1901 is assigned to the synonymy of S. antarctica Hartlaub, 1901. Campanularia subantarctica Millard, 1971 is considered as a junior synonym of C. lennoxensis Jäderholm, 1903, and data on both the male and female gonothecae are provided. A variant of Clytia gigantea (Hincks, 1866) with smaller hydrothecae than usual is described. Sertularella sanmatiasensis El Beshbeeshy, 1991 is recorded from Chile for the first time. Although not belonging to the present collection, several notes on Kirchenpaueria curvata (Jäderholm, 1904) are provided.